Significance of Binaural Synthesis on the Spatial Acoustic Impression of Enclosures - ALONSO, Alicia; MURILLO-GÓMEZ, Diego Mauricio (Archives of Acoustics, 2018)
Listening tests have been carried out to quantify the significance of binaural auralization over monaural auralization in accordance with the acoustic properties of the enclosure. To this end, acoustic rendering of three different rooms were generated based on synthesized monaural (two channels with the same audio material) and binaural room impulse responses. The auralizations were evaluated by means of subjective tests using headphones with non-individualized equalization. Parameters, such as localization, spatial impression and realism, were taken into consideration to determine the relevance of providing binaural information for the auralization of a given room. The analysis of the data has been conducted following a statistical approach based on ANOVA and Pearson correlation. The results indicate that spatial perception is strongly dependent on the acoustic characteristics of the rooms and on the listening condition of the audio material. Furthermore, as expected, advantages of binaural rendering in terms of source localization was also confirmed.